Kajian Penambahan Bakteri Probiotik Lokal Dengan Interval Waktu Inkubasi 8 Jam Terhadap Perubahan Kadar BOD dan COD Pada Air Buangan Industri Tahu - Budi Utomo; Koosdaryani Soeryodarundio; Hendy Sugiharto (Jurnal Kendali Teknik dan Sains, 2024)
Tofu has become one of the most popular foods among the people of Indonesia. This encourages the existence of a growing tofu manufacturing industry. However, the growth of this industry also results in a lot of waste being generated. If the waste is not treated properly, it can cause pollution because it contains very high BOD and COD levels. One of the ways that researchers do is by utilizing local probiotic bacteria to help reduce BOD and COD levels. Data analysis in this study is in the form of statistical analysis, where statistical data will be presented with graph/diagram methods that show the results of differences in BOD and COD values in Tofu Industry Wastewater before and after treatment. Based on the results of the study, there was a significant decrease in BOD and COD levels due to the addition of local probiotic bacteria. The efficiency of the largest decrease in BOD levels was 79.88% in the sample variation with a probiotic content of 75% when the incubation time interval was 32 hours. Meanwhile, the largest decrease in COD levels also occurred in the same sample variation with an efficiency of 74.76%.